Clinical Cases of Gallstone Ileus - O. V. Galimov; V. O. Khanov; F. R. Nagaev; R. R. Sayfullin; D. M. Minigalin; G. I. Vagizova (Креативная хирургия и онкология, 2021)
Background. Gallstone ileus is a rare complication of cholelithiasis accounting for 0.3–2.1% total acute intestinal obstructions. The recent years are witnessing a sharply elevated incidence of cholelithiasis and its entailed complications. The major diagnostic biases are the atypical clinical presentation, instrumental and laboratory evidence, and a relative paucity of surgical cases.Aim. Highlighting to surgeons the feasibility of this rare reluctantly diagnosed form of acute small bowel obstruction.Materials and methods. The article presents the clinical observations of gallstone-induced small intestinal obstruction collected at a surgery unit of the Bashkir State Medical University Clinic. Patients had surgeries for cholecystoduodenal fistula embolisation, gastro/enterotomy and lithoextraction followed by gastro/enterotomy wound suturing.Results and discussion. Patients had a benign postoperative period are were discharged in a satisfactory condition on day 7–10 after surgery for outpatient surveillance.Conclusion. Surgeons need to contemplate this pathology to ensure timely diagnosis and treatment, as well as avoid possible complications. Mostly important still is a timely gallbladder resection upon diagnosing cholelithiasis via laparoscopic cholecystectomy as a “gold standard” in treatment for this disease.